Actionable molecular alterations in advanced gynaecologic malignancies: updated results from the ProfiLER programme. (September 2019) - Varnier, Romain; Le Saux, Olivia; Chabaud, Sylvie; Garin, Gwenaëlle; Sohier, Emilie; Wang, Qing; Paindavoine, Sandrine; Pérol, David; Baudet, Christian; Attignon, Valéry; Pissaloux, Daniel; Heudel, Pierre; et al.
Abstract: Objectives: The objectives of this study were to identify actionable genomic alterations in the gynaecological subpopulation of the ProfiLER programme and to report clinical efficacy of recommended targeted treatment (RTT). Methods: The ProfiLER programme (NCT01774409) is a multicentric prospective trial aiming to implement molecular profiling in patients with advanced refractory cancers. In this programme, tumour DNA is analysed by targeted next-generation sequencing (69 genes) and by whole genome array comparative genomic hybridisation. Clinical cases and genomic profiles are presented in a dedicated molecular tumour board to guide treatment strategies. We report here an analysis of patients with gynaecological cancers included in this trial. Results: From February 2013 to February 2017, 309 patients with gynaecologic cancer were included; 279 (90%) had sufficient quality, and 131 patients (42.4%) had at least one actionable genomic alteration in cancer cells. Four alterations were shared by at least 3% of the patients: 27 (9.7%) PIK3CA mutations, 15 (5.4%) KRAS mutations, 11 (3.9%) ERBB2 amplifications and 9 (3.2%) CDKN2A deletions. Forty-one treatments were initiated among 39 patients (12.6% of the screened population): 8 (20%) had a partial response, and other 10 (24%) had a stable disease. The median progression-free survival was 2.7 months. The median overall survival was 15.6 months for patients who received a RTT. Conclusion: Molecular profiling identified actionable alterations in 42.4% of patients with advanced refractory gynaecologic cancer, but only 12.6% were treated with a RTT. Among them, 46% derived clinical benefit (5.8% of the screened population). Highlights: Analysis of somatic genomic alterations was feasible in routine practice in gynecologic oncology. Actionable genomic alterations were identified in 42.4% of patients with advanced relapsed gynecologic malignancies. Recommended targeted therapies were initiated by 12.6% of patients. Out of the 41 RTT lines initiated, eight (20%) had a partial response and other ten (24%) had a stable disease.